Effect of Neurorepair for Motor Functional Recovery Enhanced by Total Saponins From Trillium tschonoskii Maxim. Treatment in a Rat Model of Focal Ischemia - Yang, Le; Lei, Jian-feng; Ouyang, Jun-yao; Li, Man-zhong; Zhan, Yu; Feng, Xue-feng; Lu, Yun; Li, Ming-cong; Wang, Lei; Zou, Hai-yan; Zhao, Hui (Frontiers in Pharmacology, 2021)
Trillium tschonoskii Maxim. (TTM), is a perennial herb from Liliaceae, that has been widely used as a traditional Chinese medicine treating cephalgia and traumatic hemorrhage. The present work was designed to investigate whether the total saponins from Trillium tschonoskii Maxim. (TSTT) would promote brain remodeling and improve gait impairment in the chronic phase of ischemic stroke. A focal ischemic model of male Sprague-Dawley (SD) rats was established by permanent middle cerebral artery occlusion (MCAO). Six hours later, rats were intragastrically treated with TSTT (120, 60, 30 mg/kg) and once daily up to day 30. The gait changes were assessed by the CatWalk-automated gait analysis system. The brain tissues injuries, cerebral perfusion and changes of axonal microstructures were detected by multimodal magnetic resonance imaging (MRI), followed by histological examinations. The axonal regeneration related signaling pathways including phosphatidylinositol 3-kinases (PI3K)/protein kinase B (AKT)/glycogen synthase kinase-3 (GSK-3)/collapsin response mediator protein-2 (CRMP-2) were measured by western blotting. TSTT treatment significantly improved gait impairment of rats. MRI analysis revealed that TSTT alleviated tissues injuries, significantly improved cerebral blood flow (CBF), enhanced microstructural integrity of axon and myelin sheath in the ipsilesional sensorimotor cortex and internal capsule. In parallel to MRI findings, TSTT preserved myelinated axons and promoted oligodendrogenesis. Specifically, TSTT interventions markedly up-regulated expression of phosphorylated GSK-3, accompanied by increased expression of phosphorylated PI3K, AKT, but reduced phosphorylated CRMP-2 expression. Taken together, our results suggested that TSTT facilitated brain remodeling. This correlated with improving CBF, encouraging reorganization of axonal microstructure, promoting oligodendrogenesis and activating PI3K/AKT/GSK-3/CRMP-2 signaling, thereby improving poststroke gait impairments.